Cell permeation using core-shell magnetoelectric nanoparticles. Issue 174 (1st September 2016) - Betal, Soutik; Dutta, Moumita; Shrestha, Binita; Cotica, Luiz; Tang, Liang; Bhalla, Amar; Guo, Ruyan
ABSTRACT: Nano-electroporation on biological cell membrane using core shell magnetoelectric nanoparticles (CSMEN) has been discussed in this paper. Pulsed electric field created by the CSMEN in presence of a.c. magnetic field interacts with the polar phosphate heads of the phospholipid bilayer membrane when they are sub-micron distance apart. This interaction primarily results in electrostatic repulsion between the negative phosphate heads and negative pulse electric field created by core-shell magnetoelectric nanoparticles. The repulsion forces the phospholipids to dislocate from their position resulting in opening of volcano shape nanopore on the cell membrane. This study will broadly demonstrate the potential of CSMEN for application as nano-probe or fluorescent dye marked probes for electroporation experiments and for the ultimate goal of achieving efficiently targeted drug delivery applications.